An Aligned Patterned Biomimetic Elastic Membrane Has a Potential as Vascular Tissue Engineering Material - Tan, Juanjuan; Bai, Jing; Yan, Zhiqiang (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular is the leading cause of death worldwide, with an annual mortality incidence predicted to rise to 23.3 million worldwide by 2030. Synthetic vascular grafts as an alternative to autologous vessels have shown satisfactory long-term results for replacement of large- and medium-diameter arteries, but have poor patency rates when applied to small-diameter vessels. Nanoparticle (NPs) with low toxicity, contrasting agent properties, tailorable characteristics, targeted/stimuli-response delivery potential, and precise control over behavior (via external stimuli such as magnetic fields) have made it possible their use for improving engineered tissues.For polymeric nanoparticles (PNPs), formulation, size, shape and mechanical strength s and so on are among the features which can be adjusted for versatile purposes in tissue-engineered vascular graft. Poly (styrene-block-butadiene-block-styrene) (SBS) is a kind of widely-used thermoplastic elastomer with good mechanical properties and biocompatibility. Here, we synthesized anthracene-grafted SBS (SBS-An), and formed the patterns on the surface of SBS-An under UV light irradiation. And then, those were chosen as the polymer matrix working as cell sheet to observe the effect of the patterned surface on the HUVECs. By irradiating the film for different time (0s, 10s, 20s, 30s, 60s, 120s), we obtained six well-ordered surface patterned biomimetic elastic membranes with different height in the thickness direction. All six membranes were found to be non-toxic against HUVECs. Among of them, sample-20s, 30s and 60s stimulated adhesion and proliferation of HUVECs, and expression of angiogenic genes compared with sample-0s. These findings suggest a future potential use of biomimetic elastic membrane in vascular tissue engineering application.